Yoga pada Anak di TK Nusantara - Wati, Ambar; Viviana, Desi; Sofiyanti, Ida; Isfaizah (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
The aim of this sevice is to increase the learning concentration of preschool aged children by implementing  childrn’s yoga. This service was carried out at TK Nusantara on Saturday 15 Juni 2024 at 08.00-09.00 for 35 students. This activity begins by providing education about children’s yoga and teaching children yoga movements which include ballon breathing, bee breathing, butterfly posture, dragon posture, star posture, aiplane posture. Snake posture, silent relaxation and fruit meditation. Result is the service went smoothly and the children’s enthusiasm was high in doing children’s yoga movements, Children’s yoga can increase learning concentration in preschool children and teachers are expected to dot his yoga in ice breaking sessions during class time to refresh children’s brains. Abstrak Tujuan pengabdian ini adalah untuk meningkatkan konsentrasi belajar anak usia prasekolah dengan penerapan yoga anak. Pengabdian  ini dilakukan di TK Nusantara pada hari Sabtu tanggal 15 Juni 2024 pukul 08.00-09.00 sebanyak 35 siswa. Kegiatan ini dimulai dengan memberikan edukasi tentang yoga anak dan mengajarkan anak gerakan yoga yang meliputi napas balon, napas lebah, postur kupu-kupu, postur naga, postur bintang, postur pesawat, postur ular, relaksasi diam dan meditasi buah. Pengabdian berjalan dengan lancar dan antusiasme anak tinggi dalam melakukan gerakan yoga anak dan meningkatkan konsentrasi belajar anak melalui yoga anak. yoga anak mampu meningkatkan konsentrasi belajar pada anak usia prasekolah dan diharapkan guru melakukan yoga ini di sesi-sesi ice breaking jam pelajaran untuk merefresh otak anak.